ACCOUNTABILITY AND GOOD GOVERNANCE IN ISLAMIC EDUCATIONAL MANAGEMENT: A LIBRARY STUDY - Juhji Juhji; Encep Syarifudin; Shobri Shobri; Hidayatullah Hidayatullah (MANAGERE : Indonesian Journal of Educational Management, 2020)
This paper aims to explore the concept of accountability and good governance in the management of Islamic education. This research uses a qualitative approach for library research type. The discussion data was obtained from primary and secondary data derived from books and journals of international and national reputable. Content analysis is used as an analysis technique. The results of the study show that accountability and good governance in Islamic education management is the obligation of schools to account for the management, control of resources, and the implementation of policies entrusted to institutions in order to achieve the goals that have been set. The study recommends schools to implement accountability and good governance in Islamic education management.